Observation of prompt J/psi meson elliptic flow in high-multiplicity pPb collisions at root s(NN)=8.16 TeV - Yetkin, Elif Aslı (ELSEVIER, 2019)
A measurement of the elliptic flow (v(2)) of prompt J/psi mesons in high-multiplicity pPbcollisions is reported using data collected by the CMS experiment at a nucleon-nucleon center-of-mass energy root s(NN)= 8.16 TeV. Prompt J/psi mesons decaying into two muons are reconstructed in the rapidity region in the nucleon-nucleon center-of-mass frame (y(cm)), corresponding to either -2.86 < y(cm) < -1.86 or 0.94 < y(cm)< 1.94. The average v(2) result from the two rapidity ranges is reported over the transverse momentum (p(T)) range from 0.2 to 10 GeV. Positive v(2) values are observed for the prompt J/psi meson, as extracted from long-range two-particle correlations with charged hadrons, for 2 < p(T) < 8 GeV. The prompt J/psi results are compared with previous CMS measurements of elliptic flow for open charm mesons (D-0) and strange hadrons. From these measurements, constraints can be obtained on the collective dynamics of charm quarks produced in high-multiplicity events arising from small systems. (c) 2019 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Heavy-ion physics; Correlation; Flow; pPb; Heavy flavor